Implikasi Profesionalisme Guru Pendidikan Agama Islam (PAI) dalam Al-Qur’an Surat At-Taubah Ayat 122 Tentang Kewajiban Belajar (Indo-MathEdu Intellectuals Journal, 2024)
The obligation of Islamic Religious Education (PAI) teachers to deepen religious knowledge, pursue knowledge, then practice and teach it to others involves all Muslims as educational subjects, both themselves, their families, and the surrounding community. The Qur'an Surah At-Taubah verse 122 emphasizes the importance of education and teaching. This study aims to find out the Professionaloanal implications of this verse emphasizing the division of roles and responsibilities among Muslims to benefit each other for survival. This research is a type of library research or literature research. The data sources that will be used in this study include (1) books and journals about the professionalism of PAI teachers, and (2) literature on the concept of education in Islam. The results of the analysis show that developing students' potential to acquire knowledge, understanding, and form patterns of behavior and independent personalities based on Islamic values. This verse also emphasizes the obligation of Muslims to deepen their knowledge, understand their respective roles, be responsible, and teach the knowledge gained to others